PENANAMAN NILAI PEDULI LINGKUNGAN DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Yeni Lestari (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This study aims to describe the cultivation of environmental caring values in science learning in high school students of N Bhayangkara Elementary School year 2016/2017 and describes the supporting factors and their inhibitors. This research is a qualitative descriptive research. Techniques of collecting data using interviews, observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and conclusions. Validity checks data using source triangulation, technique, and time. The results showed that teachers in planning science learning include habituation, exemplary and learning while doing. The steps taken by the teacher include: using learning media and environment as a place of learning. Teachers in conducting assessments focus more on affective judgments. Supporting factors: the performance of teachers, principals and gardeners in guiding students and the existence of learning media that allows students to understand the value of environmental care. Inhibiting factors: lack of learning time of science and family role in instilling environmental caring value.